Vegetation and climate changes over the last 30 000 years on the Leizhou Peninsula, southern China, inferred from the pollen record of Huguangyan Maar Lake. (15th February 2017) - Meng, Yuting; Wang, Weiming; Hu, Jianfang; Zhang, Jixiao; Lai, Yangjun
Abstract : A pollen record from Huguangyan Maar Lake documents regional palaeovegetation and palaeoclimate changes in southern China over the last 30 000 years. Huguangyan Maar Lake is located close to the South China Sea (SCS) coastline and is influenced by the East Asian Monsoon (EAM). The pollen assemblages show a succession of vegetation and climate changes. During the Last Glaciation, 30–15.8 cal. ka BP, the Huguangyan area was dominated by subtropical evergreen‐deciduous forest with grassland surrounding the lake, indicating a colder and drier climate than today. During 15.8–11 cal. ka BP, the study area experienced several climatic fluctuations. From 11 to 2 cal. ka BP, the climate shifted to warmer and wetter conditions. After the Holocene Optimum in the early Holocene, the temperature and precipitation decreased. The sediment record of the last 2000 years cannot be used to interpret natural palaeoclimate changes due to the intense anthropogenic influences. Overall, however, the Huguangyan pollen archive highlights the rapid responses of subtropical vegetation to insolation changes in southern China.